Orthodontic Management of Skeletal Class-II Malocclusion with Horizontally Impacted Maxillary Canine: A Case Report - Gupta, Sanjay Prasad; Rauniyar, Shristi (Europasian Journal of Medical Sciences, 2021)
Management of skeletal class II relation in growing patient require careful evaluation of growth status, proper diagnosis and treatment plan to address the patient’s need. Twin block is the appliance of choice among functional appliance to correct the skeletal class II malocclusion due to its acceptability by the patient and simplified design. Maxillary canine impaction is the second most prevalent impaction after the third molars. Treatment of maxillary canine impaction is usually a challenge to orthodontic approach as the defect lies in the esthetic region of the jaw. This case report describes the orthodontic management of a 9 years male patient having skeletal Class II malocclusion with horizontally impacted maxillary canine. Some modifications in the treatment mechanics are deemed essential to address the patient’s need for achieving the optimal esthetic and to improve the occlusion. Twin block is beneficial for the treatment of skeletal malocclusion in a growing patient to achieve the maximum benefit. The orientation of impacted teeth may change from horizontal to favorable one, hence it should be considered a viable treatment alternative. In such case, early diagnosis and interception at the right time along with radiographic follow-ups are necessary to achieve successful results.